Declines in scavenging by endangered vultures in the Horn of Africa - Buechley, Evan R.; Murgatroyd, Megan; Ruffo, Alazar Daka; Bishop, Rebecca C.; Christensen, Tara; Marra, Peter P.; Sillett, T. Scott; Şekercioğlu, Çağan Hakkı (The Journal of wildlife management, 2022)
Scavenging is an important ecological process. By quickly locating and consuming carrion, vertebrate scavengers cycle nutrients, stabilize food webs, and may help mitigate disease transmission to humans. Across Africa, many scavengers feed at abattoirs (i.e. slaughterhouses), thereby aiding in waste removal. Little information exists on the scavenger community composition and dynamics at abattoirs, and, to our knowledge, the carrion removal that scavengers provide at these sites has never been quantified. We studied vertebrate scavenger ecology at 6 abattoirs in Ethiopia with time-lapse photography and in-person surveys from 2014–2019. Specifically, we investigated daily, seasonal, and inter-annual patterns in use of abattoirs by vertebrate scavengers and estimated carrion consumption rates. We demonstrated the importance of abattoirs for supporting a large number and diversity of scavenger species, including 3 critically endangered, 2 endangered, 1 vulnerable, and 2 regionally endemic bird species. At the start of the study, vultures contributed 57% of carrion removal provided by vertebrate scavengers. Detections of critically endangered Rüppell’s (Gyps rueppelli) and whitebacked (G. africanus) vultures declined by 73% and critically endangered hooded vultures (Necrosyrtes monachus) declined by 15% over the study period. Simultaneously, the detections of dogs more than doubled. Using estimates of species-specific carrion consumption rates from the literature, coupled with changes in scavenger detections in our study, we estimated a 12% (54 kg/day) reduction in carrion consumption, or nearly 20,000 kg carrion less consumed per year by the end of the study at these 6 abattoirs. Our results indicate that ongoing vulture declines across Africa could significantly reduce carrion removal. We recommend that improving fencing around abattoir facilities could help restrict access by feral dogs, increase foraging by vultures, and, therefore, increase overall carrion removal rates.